2011
DOI: 10.1016/j.jpainsymman.2011.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization and Depression in Patients With Advanced Cancer: Validation of the German Version of the Demoralization Scale

Abstract: Results provide further evidence that the DS is a valid and reliable instrument of high clinical relevance in patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
186
4
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(227 citation statements)
references
References 26 publications
28
186
4
9
Order By: Relevance
“…In each of the five studies, the correlation design was stated and five articles clearly described the representativeness of the exposed cohort. 1,2,10,18,23 Four of the five articles, thus the majority, clearly described the comparability of cohorts on the basis of the design or analysis and self-report. 2,10,18,23 One of the five studies did not clearly describe the reason for sample dropout.…”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In each of the five studies, the correlation design was stated and five articles clearly described the representativeness of the exposed cohort. 1,2,10,18,23 Four of the five articles, thus the majority, clearly described the comparability of cohorts on the basis of the design or analysis and self-report. 2,10,18,23 One of the five studies did not clearly describe the reason for sample dropout.…”
Section: Study Qualitymentioning
confidence: 99%
“…Most participants were patients with advanced cancer. In addition to depression, the research variables of the 5 studies that explored relevant factors of demoralization included psychological concepts such as anxiety, 23 hopelessness, 1,2,10 desire for death, 2,10,18 and comfort. 18 Of the 5 studies, four employed the same Demoralization Scale (DS) to measure demoralization concepts.…”
Section: Research Participants and Measurement Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Moreover, the Demoralization Scale is a measure specifically developed for use in patients with advanced cancer, assessing the demoralization syndrome as an expression of existential distress and has shown good psychometric qualities. 41,42 Limitations In comparison to the original dichotomously rated BHS, the German BHS uses a Likert-scale format. Different response categories can influence the psychometric properties of scales.…”
Section: Factor Structure Of the Bhs In German Cancer Patientsmentioning
confidence: 99%
“…Results regarding age, gender, and treatment phase are inconsistent, however. Positive [16], negative [12], [17], [19], or no associations with age [15], [20] were found. Most studies found no gender differences [12], [15], [16], [20], except for one study [17].…”
Section: Introductionmentioning
confidence: 99%